EVALUATION OF ECOTOURISM RESOURCES THROUGH PARTICIPATORY GEO-SPATIAL APPROACH : A CASE OF THE BIGER CITY, MONGOLIA - Suvdantsetseg, Balt (ITB Journal Publisher, LPPM ITB, 2011)
This paper demonstrated Participatory Geospatial Approach (PGA) to collect data and to examine the potential of existing resources for ecotourism development planning in the Biger, Gobi-Altai province, Mongolia. It attracts visitors its natural health resort services and quiet relaxing environment that it is one of Mongolia’s tourism icons. Through participatory inventory approach, tourism geospatial database was established and mapped tourism resources. Evaluation analysis were examined the potentials of the resources and characteristics of the sites in spatial pattern for proposed development which to assist decision-makers. We investigated 27 potential resource sites which have high value of attraction diversity, poor level of accessibility, high activity of community’s participation, low capacity of supporting facilities and low level of environmental impacts. The research findings illustrate the local tourism geo-database yielded by alternative methods and also demonstrate their utility to local and regional planning managers to recognize areas with tourism development potential.